X'Y'Z' + XYZ reads as "not X, not Y, and not Z, OR X, Y, and Z". By simple evaluation, we see that if you plug in 0 for X, X' becomes true and the expression simplifies to Y'Z'. If you plug in 1, X is true and the expression simplifies to YZ.
A similar thing happens if you only substitute for Y: Y=0 $\to$ X'Z', Y=1 $\to$ XZ. If Y=X', the expression evaluates to zero since XY=0 and X'Y'=0, regardless of Z. If Y=X, then the expression evaluates either to Z if X=Y=1 or Z' if X=Y=0.
In other words, it's all or nothing; the expression evaluates to 1 if X=Y=Z, regardless of whether the value of all three is 1 or 0. If any one of the three does not equal the others, the expression evaluates to zero.